2015
DOI: 10.1126/science.aaa5838
|View full text |Cite
|
Sign up to set email alerts
|

BMP gradients: A paradigm for morphogen-mediated developmental patterning

Abstract: BACKGROUND: Classic embryological studies showed that diffusible factors (morphogens) influence cell fate during dorsal-ventral (DV) axis patterning. Subsequently, mathematical analyses applied reaction-diffusion equations in a theoretical framework to model how stable gradients of morphogenetic factors might be created in developing cell fields, according to the laws of physical chemistry. This work suggested mechanisms by which such gradients form and are read in a threshold-dependent fashion to establish di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
252
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(256 citation statements)
references
References 115 publications
(102 reference statements)
2
252
2
Order By: Relevance
“…The etiology of these deficits remains enigmatic to date. Precise regulation of BMP, Wnt, and Ras/ERK signaling is crucial to normal brain development (39)(40)(41)(42), raising the possibility that genotype might influence neurocognitive outcome, as appears to be the case for congenital heart disease (22,23). The results provide a means of stratifying non-syndromic patients to assess the extent to which specific genotypes contribute to neurocognitive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of these deficits remains enigmatic to date. Precise regulation of BMP, Wnt, and Ras/ERK signaling is crucial to normal brain development (39)(40)(41)(42), raising the possibility that genotype might influence neurocognitive outcome, as appears to be the case for congenital heart disease (22,23). The results provide a means of stratifying non-syndromic patients to assess the extent to which specific genotypes contribute to neurocognitive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The Chordin/BMP pathway is ancestral and conserved in bilateral animals as diverse as Drosophila, spiders, amphioxus, hemichordates, sea urchins, and vertebrates (Bier & De Robertis, 2015). We proposed that the remarkable conservation of the Hox genes (Carrasco, McGinnis, Gehring, & De Robertis, 1984) and of the BMP/Dpp, and Chordin/Sog systems between Drosophila and Xenopus suggested that these patterning systems were present in Urbilateria, the common ancestor of all bilateral animals .…”
Section: The Ancestral Chordin/bmp Morphogenetic Pathwaymentioning
confidence: 99%
“…We collaborated with F. Michael Hoffman and Edwin "Chip" Ferguson, who had independently cloned sog, to show that microinjected chordin and sog mRNA induced neural tissue both in Drosophila and frog embryos (Holley et al, 1995). This led to the realization that we had discovered an ancient D-V patterning molecule that had been conserved during evolution between fruit fly and amphibian embryos (reviewed in Bier & De Robertis, 2015;De Robertis, 2008). Importantly, the phenotypic effects of sog mutations were known to be enhanced when the dosage of dpp/BMP4 genes was increased in Drosophila (Ferguson & Anderson, 1992).…”
Section: The Cloning Of Chordinmentioning
confidence: 99%
“…Morphogens are diffusible factors that influence developmental patterns by forming gradients, which specify different fates for cells (Bier and De Robertis 2015). Thus, BMPs exert their actions in a dose‐dependent fashion.…”
Section: Introductionmentioning
confidence: 99%